2017
DOI: 10.1155/2017/8905637
|View full text |Cite
|
Sign up to set email alerts
|

Combining Upper Limb Robotic Rehabilitation with Other Therapeutic Approaches after Stroke: Current Status, Rationale, and Challenges

Abstract: A better understanding of the neural substrates that underlie motor recovery after stroke has led to the development of innovative rehabilitation strategies and tools that incorporate key elements of motor skill relearning, that is, intensive motor training involving goal-oriented repeated movements. Robotic devices for the upper limb are increasingly used in rehabilitation. Studies have demonstrated the effectiveness of these devices in reducing motor impairments, but less so for the improvement of upper limb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
41
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(43 citation statements)
references
References 141 publications
0
41
0
2
Order By: Relevance
“…VR is an interactive and individualized treatment modality, which can provide sensorimotor training in enriched environments, so as to maximize patients engagement [17]. Several systematic reviews have shown the superiority of VR training with respect to usual care in improving motor function and ADL independence, mainly when VR is exploited to increase the time spent in therapy [14].…”
Section: Virtual Realitymentioning
confidence: 99%
“…VR is an interactive and individualized treatment modality, which can provide sensorimotor training in enriched environments, so as to maximize patients engagement [17]. Several systematic reviews have shown the superiority of VR training with respect to usual care in improving motor function and ADL independence, mainly when VR is exploited to increase the time spent in therapy [14].…”
Section: Virtual Realitymentioning
confidence: 99%
“…After treatment sessions, both hemorrhagic and ischemic stroke subjects showed significant improvements in lower limb and gait function [21]. Robot-aided therapy in the active-assisted mode offer highly repetitive, reproducible, interactive forms of training for the paretic upper limb, allowing easy and objective assessment of motor performance of the patient by recording biomechanical data [22]. Robotic devices significantly improve motor function in patients with long-term upper-limb deficits after stroke.…”
Section: Assistive Device or Modality In Patients With Hemorrhagic Stmentioning
confidence: 99%
“…For these patients, exercise therapy can improve not only the impairment but also the patients' daily activities and quality of life 1,2) . Recent studies have reported the effectiveness of robotic rehabilitation of paralyzed upper limbs in patients with stroke [3][4][5][6][7] . For example, Saita et al demonstrated that the Single-Joint Hybrid Assistive Limb (HAL-SJ; HAL-FS01, CYBERDYNE, Inc., Tsukuba, Japan) improved upper limb impairment in stroke patients 7) .…”
Section: Introductionmentioning
confidence: 99%